The Relationship Between Length of Hemodialysis Period, Diabetic Comorbidity, and Adequacy of Hemodialysis to the Changes of Sga Score on Hemodialysis Patients in Rsij Cp Hospital - ., Sunarti; Arifah Pujonarti, S (KnE Life Sciences, 2019)
CKD (Chronic Kidney Disease) and other chronic diseases were potential to prevalence of hospital malnutrition and caused financial burden. In CKD stage 5 performed dialysis, malnutrition increased with hypercatabolic related to disease progression or nutritional disorders during dialysis, and psychosocial issues such as depression and economic factors. Inadequacy of dialysis treatment might be an important cause of malnutrition. This study aimed to describe association between length of hemodialysis period, diabetic comorbidity, and adequacy of hemodialysis to the changes of SGA (Subjective Global Asessment) score on HD patients at RSIJ CP hospital on February and July 2017. This was a cohort retrospective study used secondary data from medical record and nutritional status screening report. Data from a total of 90 maintenance hemodialysis patients participated on this study. The inclusion criteria were being on HD for at least three month, upper 15th years old, having complete data such as social demographic, date of HD initiating, medical diagnosis, the Qb rate, dry body weight, and HD duration of eight-time HD on last observasion, SGA score and BMI (Body Mass Index) on two period (February and July 2017). There was no significant differences between the changes of SGA score to demographic variables, except to marietal status (p=0.003). There was no significant differences between the changes of SGA score to the length of HD period (p = 0.527), and to adequacy of hemodialysis (p = 0.484). exception to Diabetic comorbidity (p = 0.043). There was 73.7 % of patients with HD period > 2 years had no improvement of SGA score. There was a younger tendency in increased SGA score group (worsening) than in decreased SGA score group (48.8 + 15.4 vs 55.9 + 10.4 years), meanwhile 64.4% of patients were maintenance HD patients under 2 years periode. Increased prevalence of HD patients with worsening SGA score in younger patients which period of HD < 2 years was sign for better monitoring program and nutrition intervention. Further studies needed for correlation and regression to get dominant variables as determinant of nutritional status changes so appropriate nutritional intervention program could be delivered to improve quality of life of HD patients. Keywords: SGA score, length of hemodialysis period, diabetic comorbidity , adequacy of hemodialysis